Internalisasi Nilai-nilai Pancasila Melalui Kegiatan Menanam pada Anak Berkebutuhan Khusus - Widiastuti, Titik (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
The study focused on the internalization of Pancasila values through planting activities among 10th-grade students with special needs (ABK) in SMALB/C Samarinda to help them understand important values in daily life and to assist them in developing social, motor, and cognitive skills. In this qualitative research, data were obtained through observation activities, interviews, and documentation. The data were then reduced, presented (displayed), and verified (concluded). The results of the study found that: 1) The learning process in internalizing Pancasila values through planting activities was carried out in several stages, namely: introduction, contextualization, action, reflection, and follow-up stages. From all the stages carried out, Pancasila values that could be absorbed were: environmental care, cooperation, responsibility, independence, critical thinking, self-confidence, and pro-social. 2) Planting activities in learning are an effort by teachers to internalize Pancasila values and can be used as a fun learning approach for special needs children in 10th grade in SMALB/C Samarinda. This is evidenced by several indications, such as enthusiasm, active participation, increased social skills, increased understanding, practical skills, increased learning motivation, and positive feedback from parents. 3) In carrying out education, 10th-grade teachers in SMALB/C Samarinda act as inspirators, motivators, organizers, managers, mediators, facilitators, and evaluators.